2008
DOI: 10.1590/s0102-67202008000200004
|View full text |Cite
|
Sign up to set email alerts
|

A influência do treinamento muscular respiratório pré-operatório na recuperação de pacientes submetidos à esofagectomia

Abstract: InTRODUçãOIntervenções cirúrgicas abdominais altas e torácicas apresentam risco de complicações pulmonares no pós-operatório imediato. Em decorrência destas operações -que requerem anestesia geral -, e pelo fato da manipulação do órgão ser feita próxima aos pulmões, ocorre a diminuição da função e força muscular respiratória, paralisia diafragmática, bem como pneumonia, atelectasias, derrame pleural e pneumotórax6. Fatores extrínsecos como o tabagismo, o alcoolismo, o emagrecimento e a radioterapia pré-operató… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For the inspiratory training all participants had to perform three sets of ten daily repetitions, starting from functional residual capacity (FRC) until reaching the inspiratory capacity (IC) and hold the ball for a period of five to eight seconds 15 .…”
Section: Resultsmentioning
confidence: 99%
“…For the inspiratory training all participants had to perform three sets of ten daily repetitions, starting from functional residual capacity (FRC) until reaching the inspiratory capacity (IC) and hold the ball for a period of five to eight seconds 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The training with respiratory exercise was performed at home, with previous orientations given by a physiotherapist, through flow RI on the Respiron®, for a period of seven consecutive days. For inspiratory training, all participants should perform daily three sets of ten repetitions, starting from the Functional Residual Capacity (FRC) until reaching Inspiratory Capacity (IC) and sustaining the spheres for a period of five to eight seconds 15 . For the expiratory training, the Respiron® use was reversed.…”
Section: Methodsmentioning
confidence: 99%
“…(16) Thus, evidence suggests that the respiratory muscle training (RMT) with load increase can increase muscle strength and reduce dyspnea (19,20) improve vital capacity and decrease the length of hospitalization. (21) The influence of the RMT at the time of weaning the patient in prolonged MV is still controversial, since some authors observed shorter weaning in patients who underwent training (22,23,24) while others do not. (25,26) Few studies research regarding the use of RMT devices in optimizing weaning exists there are no clear recommendations for their use.…”
Section: Introductionmentioning
confidence: 99%